Praktik Tafsir Populer di Instagram: Analisis Hermeneutika Digital pada Akun @akal.indo - Rahmawati, Kholifah (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2025)
This study examines Qur’anic interpretation practices on the Instagram account @akal.indo from the perspective of philosophical hermeneutics. Moving beyond the view of social media tafsir as mere religious popularization, this research conceptualizes digital meaning production as an operational hermeneutical practice. Using qualitative content analysis of publicly accessible posts, the study identifies a three-stage interpretive process: discussion, reflection, and contextualization. Interpretation begins with framing contemporary problems—such as mental health, family relationships, and financial ethics—as the initial horizon of understanding. This is followed by reflective translation of Qur’anic values into the language of modern psychology and management, and culminates in contextualization, where these values are operationalized into practical principles for urban life. From a Gadamerian perspective, this dynamic represents a fusion of horizons between classical exegetical tradition and the lived experiences of digital audiences. The study concludes that digital Qur’anic interpretation on social media constitutes a problem-oriented hermeneutical model that reconstructs normative Qur’anic values adaptively within a digital communicative ecosystem.